A physiological glucocorticoid rhythm is an important regulator of brown adipose tissue function - Jan Kroon; Maaike Schilperoort; Wietse In het Panhuis; Rosa van den Berg; Lotte van Doeselaar; Cristy R.C. Verzijl; Nikki van Trigt; Isabel M. Mol; Hetty H.C.M. Sips; Jose K. van den Heuvel; Lisa L. Koorneef; Ronald J. van der Sluis; et al. (Elsevier, 2021)
Objective: Brown adipose tissue (BAT) displays a strong circadian rhythm in metabolic activity, but it is unclear how this rhythm is regulated. As circulating levels of corticosterone coincide with the rhythm of triglyceride-derived fatty acid (FA) uptake by BAT, we investigated whether corticosterone regulates BAT circadian rhythm. Methods: Corticosterone levels were flattened by implanting mice with subcutaneous corticosterone-releasing pellets, resulting in constant circulating corticosterone levels. Results: Flattened corticosterone rhythm caused a complete loss of circadian rhythm in triglyceride-derived fatty acid uptake by BAT. This effect was independent of glucocorticoid receptor expression in (brown) adipocytes and was not caused by deregulation of clock gene expression or overexposure to glucocorticoids, but rather seemed mediated by reduced sympathetic innervation of BAT. In a mouse model of hyperlipidemia and metabolic syndrome, long-term experimental flattening of corticosterone − and thus rhythm in BAT function − resulted in adiposity. Conclusions: This study highlights that a physiological rhythm in glucocorticoids is an important regulator of BAT function and essential for the maintenance of metabolic health.